Contextual determinants of psychopathology. The singularity of attachment as a predictor of mental dysfunction. (March 2018) - Alonso, Yolanda; Fernández, Javier; Fontanil, Yolanda; Ezama, Esteban; Gimeno, Alberto
Abstract: The general aim of this research is to evaluate the singular weight of attachment relationships in psychopathology, to determine the point to which these relationships cannot be subsumed by other variables that are famously related to attachment, such as experience of stressful life events, social support, and coping styles. 172 people treated in mental health centers provided data related to these four aspects and about manifestations of psychopathology. Multiple linear regression analyses determined that 51% of the variance in the level of symptomatology is explained with six variables: two related to adult attachment ( fear of rejection and abandonment in romantic relationships, and the degree of similarity to the fearful prototype ), one related to social support (family appreciation ), one to life events ( overall perceived stress ), and two to coping style ( cognitive restructuring and social withdrawal ). Fear of rejection was the variable accounting for the most variance. The findings suggest that adult attachment is a non-redundant individual factor associated with manifestations of psychological dysfunction and highlight the desirability of taking attachment history into account in clinical practice. Highlights: Adult attachment and other contextual determinants of psychopathology are compared. Fear of rejection predicts symptoms better than stressors, coping or social support. Attachment anxiety has a stronger correlation with symptoms than attachment avoidance. Adult attachment is a non-redundant factor associated with mental health.